2005
DOI: 10.1136/jnnp.2004.051136
|View full text |Cite
|
Sign up to set email alerts
|

Recovery patterns and long term prognosis for axonal Guillain-Barre syndrome

Abstract: Background: Little is known about the long term prognosis for patients the severe acute motor axonal neuropathy (AMAN) form of Guillain-Barré syndrome (GBS), unlike those with acute inflammatory demyelinating neuropathy (AIDP). Objective: To clarify the long term prognosis for patients with AMAN. Methods: Clinical recovery and outcome in 97 consecutive GBS patients were reviewed. Results: Electrodiagnostic criteria showed that 44 patients (45%) had AMAN, 33 (34%) had AIDP, and 20 (21%) were unclassified. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 32 publications
3
63
0
10
Order By: Relevance
“…Guillain-Barre Syndrome (GBS) is a progressive immune-related polyradiculoneuropathy that is the most common cause of acute and progressive generalized paralysis (1). There is still little knowledge on the biochemical and immunological markers that can be used to support the diagnosis of GBS.…”
Section: Introductionmentioning
confidence: 99%
“…Guillain-Barre Syndrome (GBS) is a progressive immune-related polyradiculoneuropathy that is the most common cause of acute and progressive generalized paralysis (1). There is still little knowledge on the biochemical and immunological markers that can be used to support the diagnosis of GBS.…”
Section: Introductionmentioning
confidence: 99%
“…Bu sendromda iyileşme dönemi birkaç hafta ile aylar içinde değişir ama aksonal dejenerasyon olmuşsa rejenerasyon için 6-18 ay ya da daha uzun süreye ihtiyaç vardır. Üç yıl ve üzerinde çok az olsa da iyileşmenin olduğu gösterilmiş-tir (11). Hastamızda aksonal dejenerasyon mevcut olduğu için, IVIG ve rehabilitasyon programına rağmen 6. ayda kısmi nörolo-jik defisit henüz devam etmekteydi.…”
Section: Discussionunclassified
“…Recovery was prolonged in AMAN type compared to AIDP but no significant difference in the final outcome of the patients was seen 12 . Italian Guillain-Barré Syndrome Study Group 6 showed that evidence of axonopathy may be independently associated with more severe disease variety and less chances of recovery.…”
Section: Studies By Rees Et Al Yuan Et Al and Rocha Et Almentioning
confidence: 95%